Management trends and outcomes of breast angiosarcoma: Is breast conservation feasible?. Issue 6 (12th July 2019) - Hasan, Shaakir; Metzger, April; Wegner, Rodney; Verma, Vivek; Hilton, Christie; Julian, Thomas; Trombetta, Mark
Abstract: We queried the National Cancer Database for nonmetastatic breast angiosarcoma, yielding 808 patients (202 de novo, 606 secondary). The median survival was 53.7 months. Secondary tumors were more likely to undergo mastectomy than de novo lesions (OR = 3.99, P  < 0.001). Treatments included lumpectomy (10%), lumpectomy/radiation (3%), mastectomy alone (73%), or mastectomy/radiation (14%), with no difference in survival ( P  = 0.68). Lumpectomy correlated with positive margin rate (OR 3.29), which was a predictor for death (HR = 2.37, P  < 0.01), along with older age, higher comorbidity scores, size >5 cm, and high‐grade disease ( P  < 0.05). While breast angiosarcoma is usually treated with mastectomy, lumpectomy may be feasible for well‐selected tumors.